Hubungan Kepemimpinan dan Motivasi Kerja Pegawai di Kantor Sekretariat Daerah Kabupaten Minahasa - Jerry Rommy Herter Wuisang; Stanny Sicilia Rawung; Jenny Nancy Kaligis (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
The major problem facing by the Regional Secretariat of Minahasa Regency is the lack of leaders’ attention to employees’ motivation and passion at work. This study aims to measure the relationship between leadership and employees’ work motivation in the Regional Secretariat Office of Minahasa Regency, North Sulawesi Province, Indonesia. It occupies a central role in advancing employees’ work motivation and passion. This study uses a quantitative method to measure leadership’s effect on employees’ motivation and work passion. Questionnaires were used as the main instrument to obtain the data. These questionnaires were distributed to all respondents in this study. This study’s population was predominantly made up of twenty-four employees in the Regional Secretariat Office of Minahasa Regency. Due to the limited population (24 employees), this study used all of the population as the samples. The results of this study showed a significant relationship between leadership and employees’ motivation. Since leadership is directing and influencing employees’ activity process, leaders should diligently extend it to their organizations utmost.